Design, development and preclinical assessment of MENAVip-ICP, a new snake antivenom with potential coverage of species in the Middle East and North Africa regions - Segura Ruiz, Álvaro (2024)
Snakebite in the Middle East and North Africa (MENA) is a public health problem whose magnitude is not fully known. Several antivenoms are available in these regions, but these formulations are designed for restricted geographical settings. Many countries do not have local production of antivenoms and must access products whose clinical performance has not been demonstrated. We hypothesize that it is possible to unify the treatment for viperid snakebites of MENA in a single antivenom formulation. Hereby we describe the design, development and preclinical evaluation of an antivenom of broad geographical coverage for this region (MENAVip-ICP). We produced this antivenom from the plasma of horses immunized with eight medically important venoms of viperid snake species from MENA. For this, we used a strategy based on two stages: first, immunization of horses with North African (NA) venoms, followed by a second immunization stage, on the same horses, with MENA venoms. We purified antivenoms from both stages: the Anti-NA and the final product Anti-MENA (MENAVip-ICP). Anti-NA was considered as intermediate formulation and was purified with the intention to study the progression of the immunoglobulin immune response of the horses. Antivenoms from both stages neutralized lethal, hemorrhagic, and procoagulant activities of homologous venoms. Compared to Anti-NA, MENAVip-ICP improved the neutralization profile of intravenous lethality and in vitro procoagulant activities of venoms. A notable finding was the difference in the neutralization of lethality when MENAVip-ICP was assessed intraperitoneally versus intravenously in the murine model. Intraperitoneally, MENAVip-ICP appears more effective in neutralizing the lethality of all venoms. Furthermore, MENAVip-ICP neutralized the lethal activity of venoms of species from other regions of MENA, Central/East Asia, and Sub-Saharan Africa that were not included in the immunization protocol. Our results showed that MENAVip-ICP neutralizes the main toxic activities induced by viperid MENA venoms at the preclinical level. Consequently, it is a promising product that could be clinically assessed for the treatment of snakebite envenomings in this region.